Froth & scum : truth, beauty, goodness, and the ax murder in America's first mass medium - Tucher, Andie (University of North Carolina Press, 1994)
Two notorious antebellum New York murder cases - a prostitute slashed in an elegant brothel and a tradesman bludgeoned by the brother of inventor Samuel Colt - set off journalistic scrambles over the meanings of truth, objectivity, and the duty of the press that reverberate to this day. In 1833 an entirely new kind of newspaper - cheap, feisty, and politically independent - introduced American readers to the novel concept of what has come to be called objectivity in news coverage. The penny press was the first medium that claimed to present the true, unbiased facts to a democratic audience. But in Froth and Scum, Andie Tucher explores - and explodes - the notion that "objective" reporting will discover a single, definitive truth